2006
DOI: 10.2215/cjn.01531005
|View full text |Cite
|
Sign up to set email alerts
|

Large Within-Day Variation in Cyclosporine Absorption

Abstract: and † Novartis Pharmaceuticals, East Hanover, New JerseyWith the recent focus of monitoring cyclosporine (CsA) therapy using measures of CsA absorption, it is important to understand published reports of diurnal variation in CsA exposure. In 10 renal transplant patients, CsA concentrations were measured 0, 1, 2, 3, and 4 h after both the morning and the evening doses and in a repeat session at least 1 wk later. Both area under the curve for the final 4 h after cyclosporine dose and cyclosporine concentrate 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Curtis et al evaluated the effect of food consumption by CsA level monitoring at both morning fasted and evening fed solid organ transplant patients. They found that removing the effect of food significantly reduced within-day variation of CsA PKs [104]. Consistency of drug administration and sampling time regarding meals is obligatory because of observations for decreased C max and AUC of calcineurin inhibitors with food consumption which may lead to increased dosage requirements [12].…”
Section: Hsct Population Specificationsmentioning
confidence: 99%
“…Curtis et al evaluated the effect of food consumption by CsA level monitoring at both morning fasted and evening fed solid organ transplant patients. They found that removing the effect of food significantly reduced within-day variation of CsA PKs [104]. Consistency of drug administration and sampling time regarding meals is obligatory because of observations for decreased C max and AUC of calcineurin inhibitors with food consumption which may lead to increased dosage requirements [12].…”
Section: Hsct Population Specificationsmentioning
confidence: 99%
“…Depending on the method by which a transplant recipient takes his or her medication, there can be wide variations in levels. The effect of food on calcineurin inhibitor absorption has been reported 15,16 and can account for much of the fluctuation in levels seen in the inpatient setting. The authors advocate a strict empty stomach immunosuppression protocol for all transplant recipients to minimize this fluctuation in levels and to ensure adequate drug exposure.…”
Section: How Should Immunosuppressive Medications Be Monitored While mentioning
confidence: 99%
“…All of the above data are from normal volunteers, as the FDA does not require generic immunosuppressive drugs to be studied in transplant recipients (1). However, concomitant food administration has the same effect decreasing TAC and CSA AUC by 30–40% (3, 4).…”
mentioning
confidence: 99%
“…The FDA requires that generics be within 80–125% of branded agents with respect to C max and AUC, as these are the standard measures of bioequivalence (1). The concept that AUC determines efficacy for calcineurin inhibitors is widely accepted and has been supported by several clinical studies in CNI’s as summarized by Curtis (4). Contrary to a popular misconception, the reduction in TAC AUC caused by food is not reflected in similar reductions in 12‐h trough levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation